Odpowiedź :
W(x)+F(x)= x³-5x²+2x-10 + 2x³+6x+7 = 3x³-5x²+8x-3
W(x)-F(x)= x³-5x²+2x-10 - (2x³+6x+7) = x³-5x²+2x-10-2x³-6x-7 = -x³-5x²-4x-17
W(x)-F(x)= x³-5x²+2x-10 - (2x³+6x+7) = x³-5x²+2x-10-2x³-6x-7 = -x³-5x²-4x-17
a
x³ - 5x² + 2x - 10 + 2x³ + 6x + 7 = 3x³ - 5x² + 8x - 3 =
= x(3x² - 5x + 8 ) - 3
b
x³ - 5x² + 2x - 10 - 2x³ - 6x - 7 = x³ - 5x² - 4x - 17 =
= x(x² - 5x - 4) - 17
x³ - 5x² + 2x - 10 + 2x³ + 6x + 7 = 3x³ - 5x² + 8x - 3 =
= x(3x² - 5x + 8 ) - 3
b
x³ - 5x² + 2x - 10 - 2x³ - 6x - 7 = x³ - 5x² - 4x - 17 =
= x(x² - 5x - 4) - 17